Discourses on pregnancy in Old Javanese Śaiva texts from the perspective of Kawi culture - Eka Guna Yasa, Putu; Arya Lawa Manuaba, Ida Bagus; Cahyadi Surya Distira Putra, I Wayan (UI Scholars Hub, 2025)
This article examines the discourse on pregnancy in the context of Kawi culture. The sources of data discussed here include texts of Śaiva persuasion across various genres and geographical areas, such as the Old Javanese Bhīṣmaprava from the Merapi-Merbabu region, the Old Javanese Bhīma Svarga from West Java, and a number of Old Javanese and Balinese texts from Bali, namely Tutur Aṅgastya Prāṇa, Śivāgama, Tutur Kanda Pat Bhūta, Dharma Kahuripan, and Uṣadha Mānak. According to their genres, these texts highlight either the theological, narrative, or practical (namely, from the perspective of healing) aspects of pregnancy. An intriguing feature is the presence of teachings other than Śaivism in the discourse on pregnancy. For instance, in the Śivāgama, which refers to Buddhist figures during the descent of gods in pregnancy, including their observances (brata), and hand gestures (mudrā). Meanwhile, the Tutur Aṅgastya Prāṇa explains that Bhagavān Aṅgastya had thoroughly studied Buddhism before explaining the origins of foetal development in the womb. Furthermore, the Uṣadha Mānak text repeatedly mentions Allah and Mohammad, who are crucial figures in Islamic theology, to treat people who often miscarry. This shows that the discourse of pregnancy eclectically adopts practices and idea stemming from different religious systems to ensure the safety and health of the foetus.